2023
DOI: 10.3390/nano13081315
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxygen Reduction Reaction of Graphene Oxide and Metal-Free Graphene in an Alkaline Medium

Abstract: Graphene is a well-known two-dimensional material with a large surface area and is used for numerous applications in a variety of fields. Metal-free carbon materials such as graphene-based materials are widely used as an electrocatalyst for oxygen reduction reactions (ORRs). Recently, more attention has been paid to developing metal-free graphenes doped with heteroatoms such as N, S, and P as efficient electrocatalysts for ORR. In contrast, we found our prepared graphene from graphene oxide (GO) by the pyrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A large surface area and high adsorption capacity are essential for hydrogen storage systems where the spillover effect plays a crucial role [19][20][21]. This effect improves the efficiency of proton transport from Pt nanoparticles to the ionomer, enhancing the performance of a graphene-based Pt electrocatalyst in PEMFC [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A large surface area and high adsorption capacity are essential for hydrogen storage systems where the spillover effect plays a crucial role [19][20][21]. This effect improves the efficiency of proton transport from Pt nanoparticles to the ionomer, enhancing the performance of a graphene-based Pt electrocatalyst in PEMFC [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, finding efficient and durable ORR electrocatalysts has become crucial. As is well known, platinum metals and platinumbased materials are still considered the most effective ORR catalysts [5]. However, due to low reserves, high costs, and poor cycle stability, Pt catalysts are difficult to meet the needs of large-scale applications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-free doped carbons have attracted significant attention as efficient electrocatalysts for the adsorption of reactive intermediates during ORR, which can effectively regulate the electron and/or spin redistribution of the carbon matrix, thereby facilitating the ORR process [4][5][6]. It is well confirmed that S-doping is beneficial for the production of electron-withdrawing/donating groups, such as SOx-C or/and C-S-C species on the carbon plane [7], thereby modulating the electronic state of adjacent carbon atoms [8].…”
Section: Introductionmentioning
confidence: 99%